PENGARUH E-COMMERCE DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA - Ririn Fitriyah; Sigit Puji Winarko; Andy Kurniawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of E-Commerce and accounting information systems as well as decision making for entrepreneurship, this study uses a quantitative method, with a sampling technique using the purposive sampling method, namely accounting students for the 2018-2020 academic year who have received the accounting study program for systems courses. information. With a sample of 95 respondents, the data collection technique in this study was to distribute questionnaires using Google Forms. The analysis used in this study is multiple linear regression analysis, using SPSS version 25. The results of this study indicate that E-Commerce and accounting information systems have a positive effect on entrepreneurial decision making.